(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Detecting hearing impairment before 6 months of age and appropriate treatment provides the best choice maximizing the critical period of hearing and thereby availing the resources to improve hearing and verbal communication skills. On the other hand late detection and treatment, leave such children with poor speech development and school achievement. Programmes that focus on detecting hearing disabilities at an early age of child help in improving the overall development of the child in cognitive, motor and social domains.